Analisis Komparatif Pendapatan Usahatani Padi Sawah Peserta Program Dan Tanpa Program Pemberdayaan Petani Melalui Teknologi Dan Informasi Pertanian - Muhammad Randhika; Made Antara; Rustam Abd Rauf (Universitas Tadulako, 2015)
The research aims were to analyze the incomes of wetland rice farming system under FEATI program and non-FEATI program in Malonas Village Damsol Sub District of Donggala District and to analyze the disparity of incomes betwen the farmers under the FEATI program and non-FEATI program in Malonas Village Damsol Sub District of Donggala District. The method used was survey in which samples were proportionally sampled. The research results showed that the average income generated from the wetland rice farming system in Malonas village Damsol Sub District of Donggala Distric were IDR 18.742.102,94 ha-1 planting season (PS)-1 and IDR 7.010.794,49 ha-1 PS-1 under the FEATI program and the non-FEATI program, respectively. The differences was IDR 11.731.308,45 ha-1PS-1 with the probability value of 0.001 <0.05 or tcounted = 8,16 > 1.98 at 95% confidence level. The production of wetland rice farming system under the FEATI program was 1767,47 kg ha-1PS-1 greater than that under the non-FEATI program with the probability value was 0.001 <0.05 or tcounted = 11,82 > 1.98 at 95% confidence level.